Parents' Weekend parents meeting and dinner in the faculty dining room of Carmichael Hall. Photo 029 - Versoy, Bethany (Tufts Archival Research Center, 2008)
Parents' Weekend parents meeting and dinner in the faculty dining room of Carmichael Hall.